Estimation of Renal Function Using Unenhanced Computed Tomography in Upper Urinary Tract Stones Patients - Li, Jiali; Xun, Yang; Li, Cong; Han, Yunfeng; Shen, Yaqi; Hu, Xuemei; Hu, Daoyu; Liu, Zheng; Wang, Shaogang; Li, Zhen (Frontiers in Medicine, 2020)
Objectives: The aim of this study was to determine whether unenhanced computed tomography (CT) imaging can estimate differential renal function (DRF) in patients with chronic unilateral obstructive upper urinary tract stones. Materials and Methods: This was a retrospective, single-center study of 76 patients, all the patients underwent unenhanced CT and nuclear renography (RG) at an interval of 4 to 6 weeks due to chronic unilateral obstructive urinary stones. Renal CT measurements (RCMs), consisting of residual parenchymal volume (RPV) and volumetric CT texture analysis parameters, were obtained using a semiautomatic method. Percent RCMs were calculated and compared with renal function determined using RG. Results: The strongest Pearson coefficient between percent RCM and DRF was reflected by RPV (r=0.957, P<0.001). Combinations of RPV and other parameters did not significantly improve the correlation compared with RPV alone (Pearson’s r=0.957 versus r=0.957, 0.957, 0.887, 0.815, and 0.956, for combinations of Hounsfield unit, parenchymal voxel, skewness, kurtosis, and entropy, respectively; all P<0.001). Percent RPV was subsequently introduced into linear regression, and the equation y = -2.66+1.07*x (P < 0.001) was derived to calculate predicted DRF. No statistically difference was found between predicted DRF using the equation and observed DRF according to RG (P=0.959). Conclusion: Unenhanced CT imaging can estimate DRF in patients with chronic unilateral obstructive upper urinary tract stones, and RG may not be necessary as a conventional method in clinical.